2009
DOI: 10.1084/jem.20082824
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expansion of T reg cells with IL-2–mAb complexes: induction of resistance to EAE and long-term acceptance of islet allografts without immunosuppression

Abstract: Via a transcription factor, Foxp3, immunoregulatory CD4+CD25+ T cells (T reg cells) play an important role in suppressing the function of other T cells. Adoptively transferring high numbers of T reg cells can reduce the intensity of the immune response, thereby providing an attractive prospect for inducing tolerance. Extending our previous findings, we describe an in vivo approach for inducing rapid expansion of T reg cells by injecting mice with interleukin (IL)-2 mixed with a particular IL-2 monoclonal antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
514
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(553 citation statements)
references
References 28 publications
33
514
1
1
Order By: Relevance
“…In favor of this hypothesis, IL-2/mAb CD25 complexes behave similarly to hIL-2 mutein BAY50-4798, containing a single mutation at amino acid 88 of hIL-2, which interacts with the CD122-binding epitope of IL-2. Thus, both IL-2/mAb CD25 complexes and BAY50-4798 do not lead to significant expansion of NK cells but instead preferentially stimulate CD25 high cells, including recently activated T cells and Tregs (7,23,27,28). Interestingly, high doses of IL-2/ mAb CD25 complexes led in this study to pulmonary edema, and a clinical study demonstrated that patients receiving BAY50-4798 experienced a similar degree of IL-2-mediated VLS as IL-2, suggesting that activation of T cells or other immune or nonimmune cells might cause VLS (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In favor of this hypothesis, IL-2/mAb CD25 complexes behave similarly to hIL-2 mutein BAY50-4798, containing a single mutation at amino acid 88 of hIL-2, which interacts with the CD122-binding epitope of IL-2. Thus, both IL-2/mAb CD25 complexes and BAY50-4798 do not lead to significant expansion of NK cells but instead preferentially stimulate CD25 high cells, including recently activated T cells and Tregs (7,23,27,28). Interestingly, high doses of IL-2/ mAb CD25 complexes led in this study to pulmonary edema, and a clinical study demonstrated that patients receiving BAY50-4798 experienced a similar degree of IL-2-mediated VLS as IL-2, suggesting that activation of T cells or other immune or nonimmune cells might cause VLS (29).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IL-2-mediated pulmonary edema was not an issue when Treg numbers were raised after a brief course of IL-2/mAb CD25 injections or with low doses of IL-2/mAb CD25 treatment. These latter approaches might be useful for the treatment of allergies, autoimmune disease, and allograft rejection (11,28,30).…”
Section: Discussionmentioning
confidence: 99%
“…1C Lower). The combination of antigen plus everolimus injection followed by injection of IL-2/IL-2 antibody complexes clearly represented the most powerful means of increasing Treg numbers, but as earlier demonstrated (20), the expanded proportion and absolute number of Tregs were not stable over prolonged time periods. Thus in contrast to the conversion enhanced by everolimus, which resulted in a nearly stable high proportion of converted Tregs up to several weeks after conversion (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…IL-2/IL-2ab complexes IL-2/IL2ab complexes do not only expand naturally generated Treg in vivo as described (20) but can also be used to expand recently in vivo converted Tregs. It was noted, however, that the injection of IL-2/ IL-2 complexes IL-2/IL-2ab complexes resulted not only in the expansion of Foxp3 + Tregs but also increased numbers of Foxp3 − , CD25 + cells.…”
Section: Resultsmentioning
confidence: 99%
“…To address the effect of adding IL-2, we used IL-2/anti-IL-2 complexes that have been demonstrated to expand Treg cells efficiently in vivo (33). Because the spleen contained a relatively large proportion of CD25 − Tfr cells (Fig.…”
Section: Il-2 Antagonizes the Formation And Maintenance Of Cd25 − Tfrmentioning
confidence: 99%